Caucasus War by the Eyes of Artist F. Roubaud - Gabdulbarovna Mukhametzyanova, Flera (2020)
The topicality of the study is due to the fact that today, both the territory and citizens of the North Caucasus are a historical phenomenon. One of the less studied historical phenomena is the integration of the Caucasus into the Russian Empire. The conquest of the Caucasus began in the early 18th century and is closely related to the Persian campaign of Peter I (1722-1723). However, historians sometimes forget the major uprisings in Chechnya and Dagestan (1877-188). It was at the same time that the Russo-Turkish War took place. At the same time, the 200,000-strong group of tsarist troops maintained calm in the region. The Caucasian War is a poorly studied phenomenon in the history of the Russian state.The annexation of the territory of the Caucasus to the Russian Empire has had both positive and negative consequences.